THE STUDY OF THE LEVEL OF THE PROFESSIONAL EXPERTISE ACCUMULATION OF SUPPORT PERSONNEL IN THE RAJAMANGALA UNIVERSITY OF TECHNOLOGY GROUP - Sarika, Thunyarut; Yamgate , Kusuma; Yongsorn, Chatupol (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This study aimed to examine the level of professional expertise accumulation among support personnel in the Rajamangala University of Technology group by using a mixed methods research design. The study was conducted sequentially, beginning with qualitative data collection through in-depth interviews with nine executives from all nine Rajamangala Universities of Technology. The qualitative findings were subsequently used to develop a questionnaire, and the data were collected from 377 support personnel. Qualitative data were analyzed using content analysis, while quantitative data were analyzed using the mean, standard deviation, and the Modified Priority Needs Index (PNIModified). The qualitative findings revealed that administrators perceived limitations among support personnel in terms of linking knowledge to real work situations, making decisions in complex situations, and adapting to change. In contrast, the quantitative results indicated that support personnel rated their own overall level of professional expertise accumulation at a high level for both current conditions and expected conditions. Considering the overall PNIModified of 0.03, the highest priority need was found in linking knowledge to real work situations, followed by decision-making in complex situations and adaptation to change, respectively. These findings suggested that although support personnel have a high perception of their own competence, there are still qualitative gaps in some competency components that need to be strengthened, especially practical competencies related to working in complex contexts. Accordingly, this study proposed development approaches for support personnel that emphasize learning through real work situations and systemic support from the organization to enhance the professional expertise accumulation of support personnel.